Development of cutting grass machine for semi autonomous mobile drive / Muhammad Izzat Hafizi Mohd Taufek - Mohd Taufek, Muhammad Izzat Hafizi (2023)
Cutting grass is a common work nowadays in order to make sure that people can tidy their own lawn or held a big event such as sports, wedding ceremony and etc. The issue with this work is that it takes a long time and a lot of manpower to lawn the entire area, especially for a large event. The goal of this project is to reduce the amount of human effort and work time required to complete a single task without stepping on the lawn, and to develop a dynamic model that can be attached to a semi-autonomous mobile drive. This project also necessitates the use of a wielding and a cutting process to create the model. As a result, a semi-autonomous grass cutting machine is developed, with the operator controlling the machine via a remote control. In conclusion, the project's goal has been met, and the authors discussed the benefits and points to consider when working on the system